Pediatric transverse myelitis. (30th August 2016) - Absoud, Michael; Greenberg, Benjamin M.; Lim, Ming; Lotze, Tim; Thomas, Terrence; Deiva, Kumaran
Abstract : Pediatric acute transverse myelitis (ATM) is an immune-mediated CNS disorder and contributes to 20% of children experiencing a first acquired demyelinating syndrome (ADS). ATM must be differentiated from other presentations of myelopathy and may be the first presentation of relapsing ADS such as neuromyelitis optica (NMO) or multiple sclerosis (MS). The tenets of the diagnostic criteria for ATM established by the Transverse Myelitis Consortium Working Group can generally be applied in children; however, a clear sensory level may not be evident in some. MRI lesions are often centrally located with high T2 signal intensity involving gray and neighboring white matter. Longitudinally extensive ATM occurs in the majority. Asymptomatic lesions on brain MRI are seen in more than one-third and predict MS or NMO. The role of antibodies such as myelin oligodendrocyte glycoprotein in monophasic and relapsing ATM and their significance in therapeutic approaches remain unclear. ATM is a potentially devastating condition with variable outcome and presents significant cumulative demands on health and social care resources. Children generally have a better outcome than adults, with one-half making a complete recovery by 2 years. There is need for standardization of clinical assessment and investigation protocols to enable international collaborative studies to delineate prognostic factors for disability and relapse. There are no robust controlled trials in children or adults to inform optimal treatment of ATM, with one study currently open to recruitment. This review provides an overview of current knowledge of clinical features, investigative workup, pathogenesis, and management of ATM and suggests future directions.